SIMULATION MODEL DEVELOPMENT FOR FIRE WATER PIPING NETWORK WITH NEWTON-RAPHSON ITERATION - Ari Ariangga Orranius Putra Patarru; Joko Waluyo; Nur Aini Masruroh (ASEAN Journal of Systems Engineering, 2021)
The oil and gas industry is an industry that possesses various risks. The most significant risk in this sector is fire. To support the oil and gas production activities, it is necessary to install permanent and non-permanent fire extinguishers to prevent and deal with fire accidents. The firewater network system has a role in supplying flow rates with a certain pressure to protect the production process in a fire. The flow rate and pressure must be able to preserve the process area. Therefore the performance of firewater network system must be monitored. Over time, the performance degradation of the firewater network system is unavoidable.  This decrease is due to scaling or leak minor at pipe and the decreasing performance of the diesel fire pump.This research aims to create a model of simulation fire water network system using newton-raphson iteration. The simulation model that is formed will be used to vary the flow rate against pressure. Based on iteration show the flow rate at platform 4 is 198.9 m3/h. The discharge variation is carried out to see the pressure on platform 4, the variation of the discharge of 2,000 m3/h gives a pressure of 150.45 psig, the variation of the discharge of 1,500 m3/h gives a pressure of 130.85 psig, and the variation of the discharge of 500 m3/h gives a pressure of 24.26 psig. The results of the discharge variation are used to see the performance of the fire water network system. Performance with a discharge of 2,000 m3/h decreased by 9.74%, and performance with a discharge of 1,000 m3/h decreased by 8.81%.